The Multicultural Counselling Competencies of Canadian Counsellors - Arthur, Nancy; Januszkowski, Tania (Canadian Journal of Counselling and Psychotherapy, 2007)
This study investigates 181 counsellors' multicultural competencies in the domains of self-awareness, knowledge, skills, and the counselling relationship. Counsellors recognized value conflicts with clients but reported difficulties resolving differences. Experience working with multicultural clients and attending professional development seminars were the strongest predictors of higher levels of multicultural competencies, followed by prior multicultural course work and case consultation.